Origin and dynamics of epileptic activity in a symptomatic case of Panayiotopoulos syndrome: Correlation with clinical manifestations - Leal, A. (2014)
Objective: The aim of the study was to demonstrate the dynamics and structure of the epileptic network and provide a tentative correlation with the clinical manifestations, in a symptomatic case of Panayiotopoulos syndrome (PS). Methods: JP, 5-year-old girl. Gestational period and developmental milestones were normal. At age 4 years, two episodes of recurrent vomiting, tonic eye deviation and consciousness impairment lasting for about 30 min occurred. Multifocal spikes were apparent over frontal areas in the EEG and MRI demonstrated an inferior parietal lobe (IPL) lesion. Results: A long-term 35-channel scalp EEG was obtained, which was processed with a Blind Source Separation algorithm. The most significant components with a dipolar field were submitted to source analysis and the recovered generators used to build the nodes of a brain network associated with each spike type. Analysis of information flow supported epileptic propagation from the left parietal lobe to both frontal and temporal lobes around spike peak. The good spatial overlap with physiological networks controlling eye movements, autonomic functions and consciousness, provides a tentative explanation to the diverse clinical manifestations of PS. Conclusions: Spreading patterns of epileptic activity form an extended network in PS. Significance: An epileptic focus in an IPL can reproduce both neurophysiological and clinical features of PS.